Estimating the effects of coordinated fiscal actions in the euro area - Shafik Hebous; Tom Zimmermann (Center for Economic Studies and ifo Institute (CESifo), 2012)
We estimate spillover effects of a fiscal shock in one member country in the euro area on outputs of the rest of the members, using a Global Vector Autoregression (GVAR) model. We compare the effects of a domestic fiscal shock with those of a similar size area-wide shock expressed as a weighted average of the fiscal shocks across all member countries. According to our estimates, the impact of an area-wide fiscal shock on output of a member country tends to be positive and larger than that of a domestic shock. Since the cost of participating in the area-wide shock is lower than the cost of a similar size domestic shock, our finding indicates the importance of coordinated fiscal actions in the euro area.
Keywords: E62; F41; F42; F15; H50; H60; 330; fiscal policy coordination; cross-border spillovers; open economy macroeconomics; European integration; Global VAR